The Depression Anxiety Stress Scales (DASS-21): do they measure anything beyond a general factor? - D. Valencia, Pablo (2019)
The overlap between depression and anxiety is a widely-replicated finding in mental health research. The Depression, Anxiety, Stress Scales (DASS-21) were developed to maximize the discrimination between these constructs. However, research suggests that DASS-21 predominantly measure an overall factor of emotional distress. In this study, DASS-21 were translated and applied to 353 university students (Mage = 20.42; 61% women) from Lima, Peru. The confirmatory factorial analysis supported a bifactor model, but additional analyses revealed that the data were essentially one-dimensional. Moreover, when the items were subjected to a bifactor exploratory analysis, some did not load into their original specific factors. The conclusion was that DASS-21 must be interpreted as a global dimension of emotional distress.